Technical review of endoscopic ultrasonography‐guided gastroenterostomy in 2017. Issue 4 (27th January 2017) - Itoi, Takao; Baron, Todd H.; Khashab, Mouen A.; Tsuchiya, Takayoshi; Irani, Shayan; Dhir, Vinay; Bun Teoh, Anthony Yuen
Abstract : Gastric outlet obstruction (GOO) can be caused by benign and malignant diseases and often leads to a reduction in patient quality of life. Lately, endoscopic ultrasonography (EUS)‐guided gastroenterostomy (EUS‐GE) has emerged. At the present time, there are three types of EUS‐GE using lumen‐apposing biflanged metal stents (LAMS): (i) direct EUS‐GE; (ii) assisted EUS‐GE using retrieval/dilating balloon, single balloon overtube, nasobiliary drain and ultraslim endoscope; and (iii) EUS‐guided double‐balloon‐occluded gastrojejunostomy bypass (EPASS). Overall technical success rate is approximately 90% regardless of technique used, although this is based on two retrospective studies only. In the EPASS procedure, the success rate of the one‐step procedure was higher than that of the two‐step procedure (100% vs 82%). Clinical success was almost uniform when stent placement was technically successful. Although there have been no‐stent induced procedural deaths, adverse events were seen in several cases. One technically failed case carried out using balloon‐assisted EUS‐GE was converted to laparoscopic gastrojejunostomy. Two failed cases in EPASS procedure improved with conservative treatment. In the present review, we show the feasibility and outcomes using novel EUS‐GE using LAMS. Clinical prospective trials with comparison to luminal enteral stents and surgical GE are warranted.